Pemanfaatan Limbah Kulit Nanas, Bonggol Jagung dan Air Cucian Beras sebagai Bahan Pembuatan Bioetanol - Mutiara Nurmawati Dewi; Santiko Wibowo; Fandy Valentino; Antonius Danny Nugroho (Annusfy : Journal of Multidisciplinary Research, 2026)
Increased energy demand and the environmental impact of fossil fuel use have driven the development of renewable energy, one of which is bioethanol. This study aims to examine the use of pineapple peel, corn cobs, and rice washing water as raw materials for bioethanol and the effect of substrate composition and fermentation time on the results obtained. The research was conducted through laboratory experiments with substrate composition variations of 1:1:1 and 2:1:1 and fermentation times of 7 and 11 days. The process included hydrolysis, anaerobic fermentation, simple distillation, and testing of bioethanol combustion heat conversion using a thermoelectric module. The results showed that the 2:1:1 composition and 7-day fermentation produced the highest volume of bioethanol. The bioethanol produced had a stable flame and could be converted into small-scale electrical energy. This study demonstrates the potential for utilizing organic waste as a sustainable renewable energy source.